Going Beyond One-Size-Fits-All Image Descriptions to Satisfy the Information Wants of People Who are Blind or Have Low Vision - Stangl, Abigale; Verma, Nitin; Fleischmann, Kenneth R.; Morris, Meredith Ringel; Gurari, Danna (ASSETS 2021, 2021)
Image descriptions are how people who are blind or have low vision (BLV) access information depicted within images. To our knowledge, no prior work has examined how a description for an image should be designed for different scenarios in which users encounter images. Scenarios consist of the information goal the person has when seeking information from or about an image, paired with the source where the image is found. To address this gap, we interviewed 28 people who are BLV to learn how the scenario impacts what image content (information) should go into an image description. We offer our findings as a foundation for considering how to design next-generation image description technologies that can both (A) support a departure from one-size-fits-all image descriptions to context-aware descriptions, and (B) reveal what content to include in minimum viable descriptions for a large range of scenarios.